2007
DOI: 10.1002/cphc.200700210
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐Picosecond Mid‐Infrared Spectroscopy of Phytochrome Agp1 from Agrobacterium tumefaciens

Abstract: The photoinduced primary reaction of the biliverdin binding phytochrome Agp1 (Agp1-BV) from Agrobacterium tumefaciens was investigated by sub-picosecond time-resolved Vis pump-IR probe spectroscopy. Three time constants of tau(1)=0.7+/-0.05 ps, tau(2)=3.3+/-0.2 ps and tau(3)=33.3+/-1.5 ps could be isolated from the dynamics of structurally specific marker bands of the BV chromophore. These results together with those of accompanying sub-picosecond Vis pump-Vis probe spectroscopy allow the extension of the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
90
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 59 publications
(100 citation statements)
references
References 34 publications
10
90
0
Order By: Relevance
“…The excitedstate decay times (43 and 170 ps) agree well with those observed in time-resolved fluorescence experiments (Fig. S4) and fall within the range of time constants observed in other Bph and Cph1 (9,10,12,19). The Lumi-R quantum yield is estimated at 0.13 ( Fig.…”
Section: Photochemistry Of P3: H/d Exchange Effects Reveal Proton-trasupporting
confidence: 84%
See 2 more Smart Citations
“…The excitedstate decay times (43 and 170 ps) agree well with those observed in time-resolved fluorescence experiments (Fig. S4) and fall within the range of time constants observed in other Bph and Cph1 (9,10,12,19). The Lumi-R quantum yield is estimated at 0.13 ( Fig.…”
Section: Photochemistry Of P3: H/d Exchange Effects Reveal Proton-trasupporting
confidence: 84%
“…Recent studies have indicated that 15Za to 15Ea isomerization of the chromophore at the C15═C16 double bond, which causes a flip of pyrrole ring D, accompanies formation of the Pfr state (6). The primary photoproduct, denoted Lumi-R, is formed on the 10-to 100-ps time scale and adopts the 15Ea configuration (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Absorption of a photon by the redabsorbing state (Pr) leads to the excited Pr* state with a strained C15ϭC16 bond. Isomerization about this bond leads to the second excited state, Lumi-R*, followed by relaxation to form the first photoproduct, Lumi-R (5,6). A proton is then transiently released, possibly from BV and possibly to the tightly bound pyrrole water or the main chain carbonyl oxygen of an adjacent residue, to form Meta-R c .…”
mentioning
confidence: 99%
“…The P r to P fr photoconversion is initiated by a rapid Z/E isomerization of the C-D methine bridge of the bilin chromophore (19 -22) leading within picosecondsto the formation of the Lumi-R intermediate (23,24). The following thermal relaxations via Meta-R A and Meta-R C intermediates to P fr proceed on the time scale of microseconds and milliseconds (25)(26)(27)(28).…”
mentioning
confidence: 99%